AKTIVITAS ANTIOKSIDAN FRAKSI RIMPANG KENCUR (KAEMPFERIA RHIZOMA) DENGAN MENGGUNAKAN METODE PEREDAMAN 1,1 DIPHENYL-2-PICRYLHYDRAZIL (DPPH) - Muhafidzah, Zahrah; Dali, Seniwati; Syarif, Rezky Amriati (Fakultas Farmasi UMI, 2018)
Kaempferia is one of the most widely used plants in society is a traditional at the medicine. Empirically Kaempferia rhizome has a special quality as a wound healer, good for digestion, antibacterial, and as an antioksidant. Based on research been conducted that Kaempferia extract has antioxidant activity. This research aimed to test antioxidant activity base on IC50 value on kaempferia rhizome fraction by the reduction method 1,1 diphenil-2-phicrylhydrazil (DPPH). The extract obtained was fractionated using a vacuum liquid chromatography method, then performed free radical reduction meansurements using UV-VIS spectrophotometry. A positive fraction of antioxidants activity is the n-hexane fraction : ethyl acetate (7:3 and 8:2). The n-hexane fraction 8:2 showed higher antioxidant activity with IC50 731.832 µg/mL. The n-hexane fraction: ethyl acetate 7:3 with IC50 829.737 µg/mL